The Influence of Service Quality and Perceived Value on Customer Satisfaction - Bachtiar, Azhar Ahmad; Isharina, Ikhtiara Kaideni (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
The increase in internet demand during and after the pandemic has opened big opportunities for internet service providers and increased the competition among them in gaining and retaining their customers. the objective of this research is to identify the effects of  service quality and perceived value on the satisfaction on IB Net customers. This explanatory research elucidates the relationship between its variables through hypothesis testing. Using probability sampling method and saturated or census sampling technique, 63 active customers of IB Net were involved as the respondents. The data analysis incorporates multiple linear regression, t-test, and F-test; all of which were performed in SPSS version 26. The results of the hypothesis testing lead to conclusions that (1) Service quality has a positive and significant effect on customer satisfaction and that (2) perceived value has a positive and significant effect on customer satisfaction. Therefore, service quality and perceived value positively influence customer satisfaction, providing important implications for IB Net in improving its service and value for its customers.